Persepsi Masyarakat Desa Bomo Blimbingsari Banyuwangi Tentang Kinerja Pemerintahan Desa Dalam Memberikan Pelayanan Kepada Masyarakat - Harjianto Harjianto; Sri Sedar Marhaeni; Leni Widiyanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The village administration system functions as a guard, guide, mobilizer and service. Village communities need services to meet needs that cannot be fulfilled by themselves. This study aims to determine public perceptions of the performance of the village government of Bomo Blimbingsari Banyuwangi in providing services to community members. This type of research is a qualitative descriptive with a phenomological approach. The subjects in this study consisted of the village administration and members of the Bomo village community. Data collection is done by observation techniques, interview techniques, and documentation techniques. Data analysis technique used is interactive analysis techniques including data collection, data reduction, data presentation, then drawing conclusions. The results of this study indicate that community perceptions of the performance of the village government of Bomo, Blimbingsari Banyuwangi sub-district in providing services to residents 76 percent of people consider that it is good enough and satisfying. This is evidenced by friendly, fast, and timely services, while 24 percent consider it less satisfactory because they must go back and forth in completing the file. The types of services provided are 1) Death Certificate; 2) SKCK Cover Letter; 3) Birth Certificate; 4) Certificate of Disability (SKTM); 5) Family Card Cover Letter; 6) Certificate of Change of Name; 7) Electricity Installation Certificate, Capable of Disadvantaged Communities; 8) Certificate of Moving House Address and Coming Certificate; 9) Certificate of Marriage (SKUN); 10) Letter of Establishment; 11) KTP Cover Letter